2018
DOI: 10.1002/jclp.22676
|View full text |Cite
|
Sign up to set email alerts
|

The vividness of imagining emotional feelings in positive situations is attenuated in non‐clinical dysphoria and predicts the experience of positive emotional feelings

Abstract: In addition to deficits in the general imagery of positive events, the attenuation of vividness of EFP in non-clinical dysphoric individuals warrants attention as a separate pathway by which non-clinically dysphoric individuals develop deficiencies of conscious positive feelings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…Furthermore, there is substantial evidence for the effectiveness of psychotherapy methods (e.g., Rational Emotive Behavior Therapy) in changing irrational beliefs ( David et al, 2018 , 2019 ). Lately, both empirical and theoretical studies have linked rigid goals in form of demandingness to dysregulated behavioral activation system (BAS) ( Tiba, 2005 ; Yıldırım and Maltby, 2021 ), increased activation after goal-attainment ( Tiba and Szentagotai, 2005 ), and exaggerated active coping in response to both adversities ( Tiba, 2010 ; Tiba and Manea, 2018a , b ). Being a well-known trans-diagnostic mechanism for emotional disorders ( Vîslã et al, 2016 ) for which we have effective treatment methods ( Trip et al, 2010 ; David et al, 2018 , 2019 ), evidence of the role of primary irrational beliefs in vulnerability to BPD may provide a strong treatment target, spurring the development of better psychological interventions for the treatment or the prevention of BPD.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is substantial evidence for the effectiveness of psychotherapy methods (e.g., Rational Emotive Behavior Therapy) in changing irrational beliefs ( David et al, 2018 , 2019 ). Lately, both empirical and theoretical studies have linked rigid goals in form of demandingness to dysregulated behavioral activation system (BAS) ( Tiba, 2005 ; Yıldırım and Maltby, 2021 ), increased activation after goal-attainment ( Tiba and Szentagotai, 2005 ), and exaggerated active coping in response to both adversities ( Tiba, 2010 ; Tiba and Manea, 2018a , b ). Being a well-known trans-diagnostic mechanism for emotional disorders ( Vîslã et al, 2016 ) for which we have effective treatment methods ( Trip et al, 2010 ; David et al, 2018 , 2019 ), evidence of the role of primary irrational beliefs in vulnerability to BPD may provide a strong treatment target, spurring the development of better psychological interventions for the treatment or the prevention of BPD.…”
Section: Introductionmentioning
confidence: 99%
“…Third, adopting an understanding of the mental simulation of feelings as mental re-activation of body sensations in imagery intervention may also bring a significant advantage for intervention. Recent research showed that felt sensations in the body are core components of feelings [ 18 , 19 ], they can be maintained as representations in working memory [ 20 ], they are attenuated in depressed individuals [ 21 ], and that prospective simulations of sensations felt in the body during feelings in positive situations are attenuated in individuals with high levels of depressive symptomatology [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The second line of research investigated psychological factors associated with vaccine hesitancy and intention to vaccinate. Various psychological factors are involved in psychological vulnerabilities to general health-related risk behaviors [ 25 , 26 , 27 , 28 , 29 , 30 ]. Furthermore, psychological factors have been revealed to play significant roles affecting vulnerabilities to particular health-related risk behaviors such as vaccination hesitancy [ 23 ].…”
Section: Introductionmentioning
confidence: 99%